2022
DOI: 10.3390/ijms23010491
|View full text |Cite
|
Sign up to set email alerts
|

Graphene–Oxide Porous Biopolymer Hybrids Enhance In Vitro Osteogenic Differentiation and Promote Ectopic Osteogenesis In Vivo

Abstract: Over the years, natural-based scaffolds have presented impressive results for bone tissue engineering (BTE) application. Further, outstanding interactions have been observed during the interaction of graphene oxide (GO)-reinforced biomaterials with both specific cell cultures and injured bone during in vivo experimental conditions. This research hereby addresses the potential of fish gelatin/chitosan (GCs) hybrids reinforced with GO to support in vitro osteogenic differentiation and, further, to investigate it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 98 publications
(122 reference statements)
1
19
0
Order By: Relevance
“…In addition to improving cell proliferation, many studies have confirmed that GO also actively promoted osteogenesis. The GO-modified porous composite scaffolds synthesized by Şelaru et al increased the expression of RUNX2 and OPN, promoted the deposition of calcifications, and enhanced osteogenic differentiation in vitro, which was consistent with the experimental results of this study. GO-modified concentric microgrooves enhanced the expression of osteogenic differentiation-related genes and proteins, probably because cell pseudopodia extended along the microgrooves, facilitating the preferential alignment of cells along the groove direction, resulting in increased cell–cell interactions .…”
Section: Discussionsupporting
confidence: 91%
“…In addition to improving cell proliferation, many studies have confirmed that GO also actively promoted osteogenesis. The GO-modified porous composite scaffolds synthesized by Şelaru et al increased the expression of RUNX2 and OPN, promoted the deposition of calcifications, and enhanced osteogenic differentiation in vitro, which was consistent with the experimental results of this study. GO-modified concentric microgrooves enhanced the expression of osteogenic differentiation-related genes and proteins, probably because cell pseudopodia extended along the microgrooves, facilitating the preferential alignment of cells along the groove direction, resulting in increased cell–cell interactions .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, in comparison to other carbon-based PTCAs, GO offers better water dispersibility than both graphene and reduced graphene oxide (rGO), resulting in low cytotoxicity [ 4 ]. In relation to this latter quality, recent publications [ 1 , 19 , 20 ] have proven GO biocompatibility at certain concentrations.…”
Section: Introductionmentioning
confidence: 97%
“…Many studies have proved that a low concentration of GO can promote cell adhesion and proliferation [ 15 , 17 ] and support the growth and osteogenic differentiation of stem cells in the field of bone tissue engineering [ 20 ]. GO has also had an overall significant positive effect on both in vitro differentiation and in vivo bone cell recruitment in the subcutaneous region [ 21 ]. A total of 0.5 wt.% GO was incorporated into fish gelatin/chitosan/genipin scaffolds, which enhanced the expression of runx2 and opn during osteogenic differentiation [ 21 ].…”
Section: Introductionsmentioning
confidence: 99%
“…GO has also had an overall significant positive effect on both in vitro differentiation and in vivo bone cell recruitment in the subcutaneous region [ 21 ]. A total of 0.5 wt.% GO was incorporated into fish gelatin/chitosan/genipin scaffolds, which enhanced the expression of runx2 and opn during osteogenic differentiation [ 21 ]. Therefore, a good way to improve the mechanical and osteogenic properties of polymers is the incorporation of GO as a nanofiller.…”
Section: Introductionsmentioning
confidence: 99%